Acute Fracture Neck of Femur Among Inpatients: Severe Injuries Which Need to be Taken Seriously. Issue 4 (December 2018) - Green, Carl M.; Zeiton, Moez; Foulkes, Katherine; Barrie, Jim
Abstract : Objectives: This study assesses fall prevention measures and subsequent incident reporting of falls resulting in an "inpatient fracture neck of femur (FNOF)" within a single NHS Trust, with the aim of identifying potential areas of improvement and changing practice within a Trust. Methods: Forty patients (mean age, 82.6 years) sustained an injury while being treated in hospital for an unrelated cause between January 2012 and June 2013. Case notes and incident reports were analyzed retrospectively. Results: Thirty-three (82.5%) of 40 patients had at least 1 fall screen on admission, with 27 patients (81.8%) identified as a fall risk. Fifteen patients (37.5%) had at least one fall before sustaining a FNOF. Fifteen falls occurred between midnight—0500 hours and only 4 falls were witnessed. Thirty-nine of 40 falls were reported, but none were rated as "severe" injuries. Twenty-eight (71.8%) of 39 patients had a root cause analysis performed for the injury, but only 10 root cause analyses (25.6%) produced an action plan. Fifty percent of patients died within 1 year of injury. Conclusion: Accurate fall risk assessments and adequate patient supervision are essential to minimize risks of falls, as the inpatient FNOF is linked to a higher mortality rate than patients injured in the community. A standardized method of analyzing such incidents and dissemination of the results of investigation are also required to reduce the risk of similar incidents from occurring within the hospital environment.